Qualitative Methods in International Relations
XII, 260 p.
Keywords: We still lack practical answers to one of the most basic questions in empirical research: How should researchers interpret meanings? The contributors take seriously the goals of both post-modernist and positivist researchers, as they offer detailed guidance on how to apply specific tools of analysis and how to circumvent their inherent limitations.